THE ROLE OF LEADERSHIP ON EMPLOYEES’ JOB PERFORMANCE - Susiana Susiana; Junaidi Junaidi; M. Yusuf Q.; Andi Nadhirah, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Improving performance and Good Corporate Governance (GCG) in line with the cental government vision. The research was born from the identification of the problem, that the disciplinary spirit of the ASN has not been well supported by strong leadership style and motivation, so that government employees (ASN) still have not fully understood the subtension of the concept of the CGG. The objectives of the study are identifying the impact of leadership styles, work discipline, and work motivation on ASN performance. 115 participants were invited in this study and Structural equation modelling (SEM) is used to examine research hypotheses.